(untitled) - Lyatkher, Victor M. (Hoboken, 2016)
This book contains a description of several models of seismic effects and examples of implementation of these models at specific sites. Using this information, scientists and engineers can design structures that are stronger, safer, and longer-lasting. It is a must-have for any scientist, engineer, or student working in or researching seismic loads and constructions with a view toward withstanding seismic activity.
Keywords: Earthquake engineering,Kỹ thuật địa chấn